2010
DOI: 10.1007/s11740-010-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Active media-based form hardening of tubes and profiles

Abstract: New requirements from the automotive industry regarding light weight design request the realization of structural parts with maximum strength over 1,000 MPa. On the other hand, demands concerning part complexity, function integration and part quality become higher and higher. The press hardening technology of boron-manganese alloyed steel for blank based part applications represent the state of the art. Typical applications are reinforcement parts in crash relevant car body structures. The consequently using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For titanium alloys, HPPF can achieve the required elongations and guarantee the small radii of the tubular components more easily than hydroforming. Neugebauer and Schieck [ 9 ] developed a device with a maximum pressure of 80 MPa. The device was mainly used to form high strength steel tubes.…”
Section: Introductionmentioning
confidence: 99%
“…For titanium alloys, HPPF can achieve the required elongations and guarantee the small radii of the tubular components more easily than hydroforming. Neugebauer and Schieck [ 9 ] developed a device with a maximum pressure of 80 MPa. The device was mainly used to form high strength steel tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that the hardness of the formed tube is locally dependent on the pressuretemperature curve, tube pre-heating temperature, and the tool temperature. Neugebauer and Schieck [19] developed a gas forming process with a maximum pressure of 80 MPa and a maximum temperature of 1000 • C for tube press hardening with integrated heat treatments to form high-strength products. Bach et al [20] heightened a pre-bent steel tube with the combination of gas forming and conductive heating.…”
Section: Introductionmentioning
confidence: 99%
“…To form Ti-alloy and high strength steel tubular component with a large expansion ratio, it is important to increase the deforming temperature and the internal pressure. Vadillo [13] and Neugebauer [14] studied the high strength steel forming process at elevated temperature and summarized the applications of high strength steel parts prepared by tube gas forming. Maeno [15] fabricated an ultrahigh strength steel hollow part by filling pressurized air high temperature deforming.…”
Section: Introductionmentioning
confidence: 99%